(untitled) (Journal of Parents and Teachers, 2017)
The dictionary defines scouting as: "Movement of youth that seeks the integral education of the individual through self-training and contact with nature." Scouting is the world’s largest youth volunteer organization, with 40 million people in 162 countries, from different cultures, languages and religions working to build a better world.